Genetic and biological hallmarks of colorectal cancer - Li, Jiexi; Ma, Xingdi; Chakravarti, Deepavali; Shalapour, Shabnam; DePinho, Ronald A (Genes & development, 2021)
Colorectal cancer has served as a genetic and biological paradigm for the evolution of solid tumors, and these insights have illuminated early detection, risk stratification, prevention, and treatment principles. Employing the hallmarks of cancer framework, we provide a conceptual framework to understand how genetic alterations in colorectal cancer drive cancer cell biology properties and shape the heterotypic interactions across cells in the tumor microenvironment. This review details research advances pertaining to the genetics and biology of colorectal cancer, emerging concepts gleaned from immune and single-cell profiling, and critical advances and remaining knowledge gaps influencing the development of effective therapies for this cancer that remains a major public health burden.Colorectal cancer has served as a genetic and biological paradigm for the evolution of solid tumors, and these insights have illuminated early detection, risk stratification, prevention, and treatment principles. Employing the hallmarks of cancer framework, we provide a conceptual framework to understand how genetic alterations in colorectal cancer drive cancer cell biology properties and shape the heterotypic interactions across cells in the tumor microenvironment. This review details research advances pertaining to the genetics and biology of colorectal cancer, emerging concepts gleaned from immune and single-cell profiling, and critical advances and remaining knowledge gaps influencing the development of effective therapies for this cancer that remains a major public health burden.